O impacto de notícias de entrada de mulheres em conselhos de administração: um estudo de evento - Caron, Filipe Nazzari (Universidade do Vale do Rio dos Sinos, 2016)
The board of director is one of the main mechanisms of corporate governance. Because its relevance, studies seek understand the profile its members and draw a parallel between their diversity and companies results. This study aims investigate the impact of the news of a new women member in the board of directors have in company value at BM&FBOVESPA. The issue is of fundamental importance, considering the concern of investors about the composition of the senior management of the company, as well as due to the growing debate about gender diversity and growth of women's participation in the labor market. In this event study, we analyzed 30 reports published between the years 2002 and 2016, announcing the entry of women in the 25 boards of different companies listed on the BM & FBOVESPA. The results of the statistical tests bring evidence that the announcement of women entering into the boards has a negative impact of 0.69% on the value of company stock on the date of the event and 0.73%, also negative, on the following day the date of the event. Furthermore, analysis of the cumulative abnormal returns presents evidence that such negative reflection occurs, significantly, between the day preceding the date of the event and the fifth day following the date of the event.
Keywords: Conselho de administração; Mulheres nos conselhos; Diversidade do conselho; Mulher na gestão; Board of directors; Women in the councils; Diversity council; Women in management